Different responses of the rhizosphere microbiome to Verticillium dahliae infection in two cotton cultivars - Tie, Zhanjiang; Wang, Peng; Chen, Weijian; Tang, Binghui; Yu, Yu; Liu, Zheng; Zhao, Sifeng; Khan, Faisal Hayat; Zhang, XueKun; Xi, Hui (Frontiers in Microbiology, 2023)
Verticillium wilt is a disastrous disease caused by Verticillium dahliae that severely damages the production of cotton in China. Even under homogeneous conditions, the same cotton cultivar facing V. dahliae tends to either stay healthy or become seriously ill and die. This binary outcome may be related to the interactions between microbiome assembly and plant health. Understanding how the rhizosphere microbiome responds to V. dahliae infection is vital to controlling Verticillium wilt through the manipulation of the microbiome. In this study, we evaluated the healthy and diseased rhizosphere microbiome of two upland cotton cultivars that are resistant to V. dahliae, Zhong 2 (resistant) and Xin 36 (susceptible), using 16S rRNA and ITS high-throughput sequencing. The results showed that the healthy rhizosphere of both resistant cultivar and susceptible cultivar had more unique bacterial ASVs than the diseased rhizosphere, whereas fewer unique fungal ASVs were found in the healthy rhizosphere of resistant cultivar. There were no significant differences in alpha diversity and beta diversity between the resistant cultivar and susceptible cultivar. In both resistant cultivar and susceptible cultivar, bacterial genera such as Pseudomonas and Acidobacteria bacterium LP6, and fungal genera such as Cephalotrichum and Mortierella were both highly enriched in the diseased rhizosphere, and Pseudomonas abundance in diseased rhizospheres was significantly higher than that in the healthy rhizosphere regardless of the cultivar type. However, cultivar and V. dahliae infection can cause composition changes in the rhizosphere bacterial and fungal communities, especially in the relative abundances of core microbiome members, which varied significantly, with different responses in the two cotton cultivars. Analysis of co-occurrence networks showed that resistant cultivar has a more complex network relationship than susceptible cultivar in the bacterial communities, and V. dahliae has a significant impact on the bacterial community structure. These findings will further broaden the understanding of plant-rhizosphere microbiome interactions and provide an integrative perspective on the cotton rhizosphere microbiome, which is beneficial to cotton health and production.